Autosomal dominant hereditary spastic paraplegia: Novel mutations in the REEP1 gene (SPG31) - Epplen Joerg T; Arning Larissa; Schlang Katharina J; Stemmler Susanne (BMC, 2008)
Abstract Background Mutations in the SPG4 gene (spastin) and in the SPG3A gene (atlastin) account for the majority of 'pure' autosomal dominant form of hereditary spastic paraplegia (HSP). Recently, mutations in the REEP1 gene were identified to cause autosomal dominant HSP type SPG31. The purpose of this study was to determine the prevalence of REEP1 mutations in a cohort of 162 unrelated Caucasian index patients with 'pure' HSP and a positive family history (at least two persons per family presented symptoms). Methods 162 patients were screened for mutations by, both, DHPLC and direct sequencing. Results Ten mutations were identified in the REEP1 gene, these included eight novel mutations comprising small insertions/deletions causing frame shifts and subsequently premature stop codons, one nonsense mutation and one splice site mutation as well as two missense mutations. Both missense mutations and the splice site mutation were not identified in 170 control subjects. Conclusion In our HSP cohort we found pathogenic mutations in 4.3% of cases with autosomal dominant inheritance. Our results confirm the previously observed mutation range of 3% to 6.5%, respectively, and they widen the spectrum of REEP1 mutations.